A redundancy-based iterative approach for avoiding joint limits application to visual servoing. - Chaumette, F.
We propose new redundancy-based solutions to avoid robot joint limits of a manipulator. We use a control scheme based on the task function approach. We first recall the classical gradient projection approach and then present a far more efficient method that relies on the iterative computation of motion that does not affect the task achievement and ensures the avoidance problem. We apply this new method in a visual servoing application. We demonstrate the validity of the approach on various real experiments as well as on the control of a virtual humanoid.
Keywords: Gradient projection; Iterative method; Joint limits avoidance; Mobile robot; Motion control; Position control; Redundancy; Virtual humanoid; Visual servoing